Pengaruh Penerapan Model Pembelajaran Investigasi Kelompok Terhadap Peningkatan Sikap Gotong Royong Siswa Dalam Mata Pelajaran Pendidikan Agama Islam di Kelas VII Sekolah Menengah Pertama Negeri 1 Tarogong Kaler - Salamudin, Ceceng; Sopiatin, Atin (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Cooperative attitude is an essential trait that students should possess. However, issues such as a lack of togetherness, minimal assistance among peers, and inadequate exchange of ideas during the learning process are prevalent. If students do not develop a cooperative attitude, they may become self-centered, less responsive, and lack empathy towards their social environment. Various approaches can be adopted to enhance students' cooperative attitudes. One effective method is the Group Investigation Learning Model. This model emphasizes group-based learning processes that train students to work together to achieve common goals. The purpose of this study is to describe the impact of applying the Group Investigation Learning Model on improving students' cooperative attitudes in Islamic Religious Education. Specifically, it examines the influence of the Group Investigation Learning Model (Variable X) on the cooperative attitude of students in the context of Islamic Religious Education (Variable Y). This research adopts a quantitative approach with a descriptive method. Data collection techniques include questionnaires, observation, and document studies. Statistical data analysis is used to process the data. The study's results indicate that \( F_{calculated} > F_{table} \), specifically 13.664 > 4.10, leading to the rejection of \( H_0 \) and acceptance of \( H_1 \). This means the independent variable (X), which is the Group Investigation Learning Model, significantly influences the dependent variable (Y), the students' cooperative attitude in Islamic Religious Education. The calculation of the coefficient of determination shows that the application of the Group Investigation Learning Model influences the improvement of students' cooperative attitudes by 26.4%, with the remaining 73.6% influenced by other factors not included in this study. Keywords : Group Investigation Learning Model, Students' Cooperative Attitude, Islamic Religious Education.